2021
DOI: 10.1186/s12944-021-01507-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biochemical aspects of salt (sodium chloride) in inflammation and immune response with reference to hypertension and type 2 diabetes mellitus

Abstract: Obesity, insulin resistance, type 2 diabetes mellitus (T2DM) and hypertension (HTN) are common that are associated with low-grade systemic inflammation. Diet, genetic factors, inflammation, and immunocytes and their cytokines play a role in their pathobiology. But the exact role of sodium, potassium, magnesium and other minerals, trace elements and vitamins in the pathogenesis of HTN and T2DM is not known. Recent studies showed that sodium and potassium can modulate oxidative stress, inflammation, alter the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 221 publications
0
3
0
Order By: Relevance
“…Recently, sodium was shown to modulate oxidative stress and inflammation, alter the autonomic nervous system, and cause innate and adaptive immune dysfunction [ 20 ]. .Many studies have shown that high sodium and chloride are directly associated with depression [ 21 ].…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…Recently, sodium was shown to modulate oxidative stress and inflammation, alter the autonomic nervous system, and cause innate and adaptive immune dysfunction [ 20 ]. .Many studies have shown that high sodium and chloride are directly associated with depression [ 21 ].…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…In adults, salt loading increased the formation of LA-related oxylipins [ 78 ]. Additionally, sodium has been hypothesized to inactivate fatty acid desaturases that synthesize ARA from LA and EPA and DHA from ALA [ 79 ]. Sodium also increases the expression of the COX2 enzyme, which synthesizes oxylipins [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immune response, and in particular, lymphocytes, seem to have a role in the pathobiology of hypertension and vascular diseases [29]. This is supported by the observation that inflammation and immune activation are involved in the pathobiology of endothelial dysfunction, hypertension, and pre-eclampsia [29][30][31]. Preeclampsia is characterized by hypertension, fluid retention, peripheral edema and headache and in some instances convulsions and is responsible for IUGR of the fetus.…”
Section: Trpm8 Trpv Channels Nociceptor Function and Immunosurveillancementioning
confidence: 91%